The MacBride Report in Twenty-first-century Capitalism, the Age of Social Media and the BRICS Countries - Fuchs, Christian (Javnost-The Public, 2015)
The MacBride Report was published in 1980. The report communicated the need for a New World Information and Communication Order (NWICO). With the breakdown of what used to be called “actually existing socialism“ in the East and with the rise of the neoliberal commodification of everything, a NWICO indeed emerged, but one that looked quite different from that the MacBride commission imagined. Thirty-five years later, it is time to ask how the situation of the media and communications in society has changed. This contribution asks the question of what we can make of the MacBride Report today in a media world and society that has seen the rise of an economically driven form of globalisation that also has impacts on the media, the expansion of the information economy with a new young precariat at its core, and the emergence of the World Wide Web and its change into a highly commercialised system, including the emergence of so-called “social media“ whose capital accumulation model is based on targeted advertising.